Catalytic Radical Process for Enantioselective Amination of C(sp3)−H Bonds. Issue 51 (16th November 2018) - Li, Chaoqun; Lang, Kai; Lu, Hongjian; Hu, Yang; Cui, Xin; Wojtas, Lukasz; Zhang, X. Peter
Abstract: A new catalytic radical system involving Co II ‐based metalloradical catalysis is effective in activating sulfamoyl azides for enantioselective radical 1, 6‐amination of C(sp 3 )−H bonds, affording six‐membered chiral heterocyclic sulfamides in high yields with excellent enantioselectivities. The Co II ‐catalyzed C−H amination features an unusual degree of functional‐group tolerance and chemoselectivity. The unique reactivity and stereoselectivity is attributed to the underlying stepwise radical pathway. The resulting optically active cyclic sulfamides can be readily converted into synthetically useful chiral 1, 3‐diamine derivatives without loss in enantiopurity. Abstract : Radicals and Co : An enantioselective radical process has been established using cobalt(II)‐based metalloradical catalysis (MRC) for stereoselective amination of aliphatic C−H bonds at room temperature to form chiral 1, 3‐diamines under neutral and non‐oxidative conditions. The cobalt(II)‐catalyzed C−H amination features an unusual degree of functional‐group tolerance and chemoselectivity.